Anemia prevalence and associated factors among students benefiting from the rural compulsory education nutrition improvement program in Jilin province in 2023: a cross-sectional study - Hongli CUI; Xingang ZHANG; Liwei ZHANG; Bo LUAN; Sijie LIU (Zhongguo gonggong weisheng)
ObjectiveTo investigate the anemia status and its influencing factors among students in the Nutrition Improvement Program areas of Jilin province, and to provide a reference for formulating targeted nutrition improvement measures. MethodsA stratified cluster sampling method was used to select a total of 2 258 primary school students (grade 3 and above) and junior high school students from two key monitoring counties implementing the "Rural Compulsory Education Student Nutrition Improvement Program" in Jilin province in 2023. Questionnaires, physical examinations, and hemoglobin tests were conducted. The chi-square test and multivariate binary logistic regression analysis were used to analyze the anemia status and its influencing factors among the students. ResultsThe anemia prevalence among primary and secondary school students in the Nutrition Improvement Program areas of rural Jilin province was 6.55%, all of which were mild (3.63%) and moderate anemia (2.92%). The anemia prevalence in girls (8.97%) was higher than that in boys (4.25%), and the difference was statistically significant (χ2 = 20.534, P < 0.001). Among boys, the detection rates of anemia differed significantly among students with different nutritional statuses and snacking frequencies (P < 0.05). Among girls, the detection rates of anemia differed significantly among students with different maternal education levels, school stages, age groups, whether they had diarrhea in the past two weeks, whether they had menstruated, frequency of dairy product consumption, snacking frequency, whether they liked the food provided by the school, whether they usually had leftover food, and daily snack expenditure (P < 0.05). Multivariate binary logistic regression analysis showed that, compared with the corresponding reference groups, overweight and obesity were protective factors against anemia in boys, while snacking 3-6 times per week was a risk factor for anemia. Consuming dairy products 3-6 times a week and ≥ 1 pack (200 mL/pack) daily were protective factors against anemia in girls, while having menstruated and having a mother with a primary school education or below were risk factors for anemia in girls. The risk of anemia in boys and girls in Dunhua city was 6.091 times and 3.309 times higher than that in Da'an city, respectively. ConclusionsThere are gender differences in the prevalence of anemia among students in the Nutrition Improvement Program areas of Jilin province. The influencing factors of anemia and the detection rates of anemia also vary by region. Individualized nutritional intervention measures are needed to improve the anemia status of students.